DEVELOPMENT OF MEDIA COMPETENCE THROUGH AN INTEGRATIVE APPROACH USING ARTIFICIAL INTELLIGENCE TOOLS (IN ENGLISH LANGUAGE CLASSES) - Tog’ayeva Muattar Bahodir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article explores the development of media competence among students through an integrative approach that incorporates artificial intelligence (AI) tools in English language classes. In the context of rapid digital transformation, media competence has become a critical skill, enabling learners to effectively access, analyze, evaluate, and create media content. The study examines how AI-powered tools—such as chatbots, automated writing assistants, and multimedia generators—can enhance language learning while simultaneously fostering media literacy. The research employs a mixed-method approach involving experimental teaching, surveys, and performance analysis. The findings indicate that integrating AI tools into English language instruction significantly improves students’ critical thinking, digital literacy, and communicative competence. The article concludes with pedagogical recommendations for educators aiming to implement AI-based integrative strategies in language classrooms.